Pentingnya pelestarian naskah kuno sebagai warisan budaya bangsa - sahidi sahidi (UIN Sumatera Utara, 2018)
As one of the written historical evidence, ancient manuscripts or manuscripts are ancestral heritage that is rich in cultural values, moral values, religious values, and social values. The ancient manuscript also describes the previous human civilization that was rich in science. The ancient manuscript is a historical reminder that should be preserved and its existence is preserved so that the next generation of the nation can also recognize the values of the information contained in the text. Preservation is the most appropriate way to maintain the existence of ancient manuscripts from obliteration. Preservation efforts are activities carried out to preserve the heritage of cultural heritage in this case the ancient manuscripts so that they are not quickly damaged and can be used in accordance with the original. This is very important to be carried out by the relevant institutions to save the priceless national assets that have so far been neglected and are still very concerning. Along with the development of increasingly sophisticated technology, preservation also undergoes a change of method, from traditional to modern techniques. This method is the most appropriate method to do than traditional methods that can have an adverse effect on the manuscript, because there are many texts that have been physically damaged. With modern methods it is hoped that ancient manuscripts can be digitized so that they can be easily accessed and read by the next generation.Keywords: preservation, ancient manuscripts, heritage, culture